Primary hepatocellular carcinoma ("hepatoid" carcinoma) of the pancreas: a case report and review of the literature. Issue 2 (13th November 2013) - Steen, Shawn; Wolin, Edward; Geller, Stephen A.; Colquhoun, Steven
Key Clinical Message We present a case of hepatocellular carcinoma located within the pancreas. These tumors occur in the body and tail of the pancreas, with a male predominance, and at a younger age. Tumors with pure hepatocellular histopathology have better survival and recurrence rates and should be offered surgical therapy if possible.